The Influence of Product Quality and Marketing Strategy Management on Consumer Satisfaction and Customer Loyalty with the Use of Wardah Skincare Products in Jambi City - Putri, Nadya Eka; Halimah, Sri; Habibi, Rifqi; Ipada, Naziroh Nurul; Labaika, Ratna; Fusfita, Nurlia; Agusriandi, Agusriandi; Dewanata, Pandu (PT Inovasi Pratama Internasional, 2024)
Beauty care has become a crucial necessity in modern society, not only for enhancing appearance but also for skin health. The inundation of the market with beauty products and advertisements creates a strong urge for individuals, especially women, to consume beauty products and services for desired appearances. In efforts to attract consumers, beauty business owners strive to provide the best services to fulfill consumer satisfaction. Consumer satisfaction becomes the primary focus for consumer- oriented companies, with consumer loyalty formed from a combination of satisfaction and complaint handling. Consumers, as key players in the business ecosystem, play a significant role in determining product acceptance in the market. Product quality is a crucial factor in creating customer loyalty, with perceived quality by customers playing a crucial role in enhancing satisfaction and ultimately strengthening customer loyalty. Therefore, a deep understanding of consumer needs and preferences, along with efforts to maintain high product quality, is key to successfully building long-term customer loyalty.